Strategi manajemen dalam meningkatkan daya saing perbankan melalui inovasi layanan mobile banking di era digital - Sabrina, Siti Nabila Zida (Maliki Interdisciplinary Journal, 2024)
The development of digital technology has significantly changed the face of the banking industry, driving the need for service innovation that can improve competitiveness. This research aims to analyze the management strategies implemented by banks in developing mobile banking services in response to the challenges and opportunities in the digital era. Through a literature study approach, this research identifies various strategies, including product differentiation and cost leadership, as well as the importance of human resource readiness in implementing innovation. The findings show that implementing innovative features in mobile banking not only improves operational efficiency, but also enhances customer experience and customer loyalty. Despite challenges such as regulation and cybersecurity, banks that are able to adapt quickly will gain a competitive advantage. This research provides insights for banking industry players to understand the importance of proper management strategies in facing competition in the digital era.